2019
DOI: 10.1111/lang.12348
|View full text |Cite
|
Sign up to set email alerts
|

Case Marking Variation in Heritage Slavic Languages in Toronto: Not So Different

Abstract: We examined case‐marking variation in heritage Polish, Russian, and Ukrainian. Comparing heritage to homeland Polish and Ukrainian speakers, we found only a few types and a few tokens of systematic distinction between heritage and homeland varieties. A total of 6,291 instances of nouns and pronouns were extracted from transcribed conversations with 62 speakers. Comparing normative forms to observed forms in logistic regression analyses showed that the form of the nominal and the case selector have significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…An interesting observation was the fact that there was comparatively little variability among all the outcome variables we measured among the later bilinguals (see Figures 1a, 1b, and 1c above), but a wide spread of scores among the earlier ones. This suggests that the early bilinguals/heritage speakers under observation in the present study are not, as has sometimes been suggested (e.g., Kupisch & Rothman, ), acquiring an attrited contact variety from the parental generation (i.e., converging perfectly on the variety of the language that they are exposed to), but have failed to fully master the more complex aspects of Turkish grammar despite having been exposed to a variety of Turkish that closely resembles that spoken in the country of origin (see also the findings reported by Łyskawa and Nagy, , on Slavic languages in Toronto).…”
Section: Discussionsupporting
confidence: 57%
“…An interesting observation was the fact that there was comparatively little variability among all the outcome variables we measured among the later bilinguals (see Figures 1a, 1b, and 1c above), but a wide spread of scores among the earlier ones. This suggests that the early bilinguals/heritage speakers under observation in the present study are not, as has sometimes been suggested (e.g., Kupisch & Rothman, ), acquiring an attrited contact variety from the parental generation (i.e., converging perfectly on the variety of the language that they are exposed to), but have failed to fully master the more complex aspects of Turkish grammar despite having been exposed to a variety of Turkish that closely resembles that spoken in the country of origin (see also the findings reported by Łyskawa and Nagy, , on Slavic languages in Toronto).…”
Section: Discussionsupporting
confidence: 57%
“…Given though, however, that these children were tested in their minority L1 (Russian or Polish) spoken primarily in the home in the context of a societal, majority L2 (Dutch or Hebrew), we believe that these children fit the definition of 'HSs' as per Kupisch & Rothman (2016) and are, therefore, reviewed here. simply as a system with a higher degree of variation but similar to what is also found in monolingual systems (Łyskawa & Nagy, 2019).…”
Section: Introductionsupporting
confidence: 54%
“…A common argument levied by those supporting some version of severe attrition (or language death) is the high rate of errors in nominal morphology among heritage speakers. In the following paragraphs, we outline a number of methodological problems stemming from the notion of a (performance) error in a HL grammar, specifically: an unjustifiable assumption that the standard form is the target output; and the idealized notion that any grammatical change over time constitutes language decay in a HL (see also e.g., Łyskawa & Nagy, ).…”
Section: Nominal Morphology: Dative Case In Heritage German Varietiesmentioning
confidence: 99%
“…A common argument levied by those supporting some version of severe attrition (or language death) is the high rate of errors in nominal morphology among heritage speakers. In the following paragraphs, we outline a number of methodological problems stemming from the notion of a (performance) error in a HL grammar, specifically: an unjustifiable assumption that the standard form is the target output; and the idealized notion that any grammatical change over time constitutes language decay in a HL (see also e.g., Łyskawa & Nagy, 2019). Benmamoun et al (2013) notes a number of studies across a variety of heritage languages that exhibit nontarget realization of nominal case in situations of language attrition, especially with languages that have both concatenate (suffixation) and nonconcatenate (word-internal modification, including vowel mutation) morphology.…”
Section: Nominal Morphology: Dative Case In Heritage German Varietiesmentioning
confidence: 99%